Balāghah analysis of the correspondence between al-Ḥajjāj ibn Yūsuf al-Thaqafī and Qaṭarī ibn al-Fujā’ah during the Battle of Dūlāb - Rizka Khairianur; Isnayni Hadianti; Fitria Dinata; R. Yaniah Wardani (Linguistics Initiative, 2026)
The Battle of Dūlāb was a conflict between the Khawārij al-Azāriqah group and the Umayyad Dynasty government, triggered by the Khawārij’s rejection of the Umayyad political and religious authority. This study aims to analyze the elements of balāghah contained in the correspondence between al-Ḥajjāj ibn Yūsuf al-Thaqafī and his adversary Qaṭarī ibn al-Fujā’ah, during this event. The research employs a qualitative method with a descriptive-analytical approach. Primary data consist of the letters exchanged between al-Ḥajjāj and Qaṭarī as found in classical sources, while secondary data are obtained from various literary works, historical documents, and relevant classical texts. The findings reveal three main results. First, from the perspective of ʿilm al-bayān, the study identifies 3 instances of tashbīh, 2 instances of majāz istiʿārah, and 2 instances of Kināyah. Second, from the perspective of ʿilm al-maʿānī, the analysis reveals 3 instances of kalām khabarī, 3 instances of kalām inshāʾī, 1 instance of qaṣr, 2 instances of iṭnāb, and 1 instance of Ījāz. Third, from the perspective of ʿilm al-badīʿ, the study identifies muḥassināt lafẓiyyah in the form of 5 instances of sajʿ, 3 instances of jinās, and 1 instance of iqtibās. In addition, muḥassināt maʿnawiyyah is represented 1 instance of ṭibāq.